Recent advances in rock magnetism, environmental magnetism and paleomagnetism : International Conference on Geomagnetism, Paleomagnetism and Rock Magnetism (Kazan, Russia) /: International Conference on Geomagnetism, Paleomagnetism and Rock Magnetism (Kazan, Russia). ([2019]) - Unknown
No abstract available